2021
DOI: 10.1080/13607863.2020.1870209
|View full text |Cite
|
Sign up to set email alerts
|

Does positive affect mediate the association of multimorbidity on depressive symptoms?

Abstract: Objectives: Multimorbidity poses various challenges, and previous research has indicated a causal relation with depression. As multimorbidity is not curable, the underlying mechanisms are of great interest. Positive affect is a major resource for coping with chronic conditions and for the prevention of depression. Long-term multimorbidity, however, may deplete positive affect. The purpose of this paper is to investigate the role of positive affect in the association between multimorbidity and depressive sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Further, evidence suggested that functional health may influences the relationship between multimorbidity and depression in older adults. The functional health might act as a mediator between an association of multimorbidity and depression by limiting the social and physical abilities of individuals [ 25 , 26 ], as multimorbidity escalates the deterioration of physical health leading to adverse emotional outcomes which facilitate depressive symptoms [ 27 , 28 ]. In addition to functional health risk factors, behavioural health issues such as alcohol consumption, smoking, physical activity are also linked with high depressive disorders [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, evidence suggested that functional health may influences the relationship between multimorbidity and depression in older adults. The functional health might act as a mediator between an association of multimorbidity and depression by limiting the social and physical abilities of individuals [ 25 , 26 ], as multimorbidity escalates the deterioration of physical health leading to adverse emotional outcomes which facilitate depressive symptoms [ 27 , 28 ]. In addition to functional health risk factors, behavioural health issues such as alcohol consumption, smoking, physical activity are also linked with high depressive disorders [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that women have a higher life expectancy, and experiences poor health in older ages [ 1 , 35 ]. As a result, older women are more vulnerable to morbidity than men because of the higher prevalence of acute, chronic, and mental disorders [ 28 , 29 , 36 ]. Studies have shown that women have a larger disease burden and the prevalence of chronic conditions increase with their age [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Future research should also exploit the potential of ecological momentary assessment studies to gain further insight into other mechanisms that support first-generation immigrants' coping capabilities. Research based on annual longitudinal analyses indicates that positive affect, might be of importance as an intermediate (Demirer et al, 2022).…”
Section: Limitations and Future Researchmentioning
confidence: 99%